Risk stratification by ultrasound and mammography for screen-detected non-palpable breast cancer in Chinese women - Xu, Ying; Yao, Ru; Lin, Yan; Mao, Feng; Zhang, Xiaohui; Shen, Songjie; Pan, Bo; Zhou, Yidong; Sun, Qiang (Frontiers in Oncology, 2025)
BackgroundMammography (MG) and ultrasound (US) are currently the ‘real-world’ initial imaging tests for breast cancer in China. Previously, we demonstrated that US and MG detected non-palpable breast cancer (NPBC) had similar survival. This study was performed to validate the hypothesis whether MG+/US- NPBC could be taken as ultra-low risk cancer.MethodFrom 2015-2018, 3,113 consecutive patients received biopsy with initial positive screening. Among them, 2,591 US positive patients underwent US-guided biopsy. Meanwhile, 371 MG+/US- patients underwent MG-guided biopsy. Clinical characteristics, treatment and 5-year disease free survival (DFS) and overall survival (OS) were analyzed. Prognostic factors of NPBC were identified.ResultsWe identified 419 cases of US+/MG-, 225 cases of US+/MG+, and 118 cases of US-/MG+ breast cancers, yielding positive predictive values (PPVs) of 21.6%, 34.7%, and 22.6%, respectively. Notably, among NPBC with US-/MG+ features, a significantly higher proportion exhibited DCIS (50.8%, P<0.001), multifocality (18.5%, P = 0.003), underwent breast-conserving surgeries (66.1%, P<0.001), and did not receive chemotherapy or radiotherapy (64.4% & 66.9%, P<0.001 & P = 0.032). MG+/US- patients demonstrated improved DFS compared to US+/AnyMG (P = 0.035), with no significant difference in OS (P = 0.48). Univariate and multivariate Cox regression analysis identified age, TNM stage, lymphovascular invasion (LVI), and estrogen receptor (ER) status as significant DFS predictors(P<0.05), with ER status alone being significant for OS (P = 0.002).ConclusionMG+/US- NPBC was associated with a favorable prognosis in this study, potentially representing an “ultra-low-risk” subtype of breast cancer that warrants further investigation. Hence US had the potential of stratifying the screen-detected NPBC into regular low risk (US+/MG+ and US+/MG-) and ultra-low risk (MG+/US-).